The good friends we make along the way: good friendship and epistemic rationality - Dacanay, Joseph Andrei Aczon (Nanyang Technological University, 2023)
A recent objection in the debate on epistemic partiality claims that epistemic partiality stems from a mistaken view of friendship. Epistemic partiality holds that we have to be epistemically irrational in order to realize good friendship due to the constitutive conflict between our epistemic and friendship norms (§1). However, the objection holds that these norms do not constitutively conflict but rather are connected (§2). Hence, the thesis follows the objection and motivates its argument from an intuitive account of friendship by Cicero that connects good friendship to epistemic rationality. The thesis argues that from the constitutive connection between epistemic and friendship norms, epistemic rationality is required of good friends in order to realize good friendship. The constitutive connection is based on epistemic virtues, which makes up our epistemic norms and is also part of our friendship norms (§3). Afterwards, the thesis considers and addresses the objections of whether we should take epistemic virtues to form our epistemic norms and rationality if close-mindedness is taken to be an epistemic virtue; and whether having more rational beliefs that comes from the good friendship itself still counts as epistemic partiality and bias (§4).